THE ROLE OF THE INTERACTIVE ENGLISH YOUTUBE CHANNEL IN IMPROVING ENGLISH LANGUAGE SKILL - I Made Prinata Kusuma; I Nengah Iwan Darmawan; Putu Chris Susanto (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2020)
ABSTRACTYouTube is one of the most visited video sharing platforms in the world. YouTube, as the number two most popular site in the world (Alexa, 2017) has also become a site that helps improve English language skills. On YouTube, we can watch various types of videos. This research explores and analyzes the types of video content uploaded by the Interactive YouTube Channel, whether there are five aspects of basic competence in English, and how their subscribers interact in the comments section whether the content is useful or not. Researchers used a descriptive qualitative research design in this study. The research findings show that the interactive English Channel uploads five aspects of Basic English competencies, namely speaking, vocabulary, pronunciation, listening, and grammar. The interaction of the subscribers was enthusiastic, with 400 positive comments submitted by the subscribers. With that many comments, Interactive English Channel took the time to reply or just to give a "like". It proves that this channel is very useful for its subscribers in improving their English language skills.Keyword: YouTube, English learning, English language skill